Progress and Future Directions of Crime Research in China with Selected Case Studies. (July 2017) - Liu, Lin; Li, Jessica C. M.
This special issue of the Journal of Research in Crime and Delinquency presents four articles that expand our theoretical and empirical understanding of crime and its prevention in contemporary China. Undertaken mostly by Chinese scholars, these articles are theory-driven inquires that utilize original data to examine critical criminological issues in transitional China. Two of the four papers were initially presented at the 2015 Conference on Crime Geography and Crime Analysis, an annual conference hosted in Guangzhou in early July each year. In addition to introducing these four articles, this paper also provides a summary on progress, challenge, opportunities and future direction of crime research in China.